Efficient perovskite solar cells by hybrid perovskites incorporated with heterovalent neodymium cations. (July 2019) - Wang, Kai; Zheng, Luyao; Zhu, Tao; Yao, Xiang; Yi, Chao; Zhang, Xiaotao; Cao, Yu; Liu, Lei; Hu, Wenping; Gong, Xiong
Abstract: Recently, hybrid perovskite materials have emerged as attractive alternatives for realizing cost-effective efficient perovskite solar cells. To date, impressive efficiency has been realized from the state-of-the-art solar cells through generic interface engineering and film morphological manipulation of perovskite active-layer in macroscopic scale. To further boost the efficiency of perovskite solar cells, microscopically tuning optoelectronic properties of hybrid perovskite materials represents a promising direction. In this study, we report efficient perovskite solar cells by a novel hybrid perovskites material that is incorporated with heterovalent neodymium cations (Nd 3+ ). As compared with pristine hybrid perovskite materials, Nd 3+ -doped hybrid perovskite materials possess superior film quality with highly reduced trap-states, significantly enlarged charge carrier lifetimes, dramatically enhanced and balanced charge carrier mobilities. As a result, planar heterojunction perovskite solar cells by Nd 3+ -doped hybrid perovskite materials exhibit highly reproducible power conversion efficiency of 21.15% and significantly suppressed photocurrent hysteresis. These findings open a new window of tuning the optoelectronic properties of hybrid perovskite materials and boosting the device performance of perovskite solar cells. 21.15% power conversion efficiency and significantly suppressed photocurrent hysteresis were demonstrated from planar heterojunction perovskite solar cell using heterovalent neodymium cation doped hybrid perovskite materials. Graphical abstract: Image 1 Highlights: Over 21% power conversion efficiency, significantly suppressed photocurrent hysteresis and highly reproducible planar heterojunction perovskite solar cells. Heterovalent neodymium cations substituted hybrid perovskite materials. Dramatically enhanced and balanced charge carrier mobilities and enlarged charge carrier lifetimes.